Characterization of Esocid Herpesvirus 1 (EsHV1) from Europe - Mikael Leijon; Charlotte Axén; Fereshteh Banihashem; Tobias Lilja; Petter Tibblin; Björn David Persson (Pathogens)
During routine sampling of northern pike, a male Esox lucius with circular blue-metallic granular spots mainly located on the head and back was identified. Histological investigations presented multifocally thickened epidermis rich in basophilic large structures with a granulated rim and a dense, non-granulated center. Other organs showed no signs of infection. Ultrastructural analysis of the skin revealed three different types of herpes-like structures predominantly located within enlarged vacuoles. PCR analysis and NGS of dissected skin tissue verified the presence of EsHV1 DNA. In this study, we describe the first identification of EsHV1 in mainland Europe. In addition, for the first time, full sequences of both the DNA polymerase and terminase of the virus is available, thus allowing for an improved phylogenetic placement of EsHV1 within the Alloherpesviridae family. In addition to the EsHV1 infected pike, we also observed that 11.1% of the pike were affected by lymphosarcoma, a hyperplasia-disease caused by retroviruses. In conclusion, viral infections in pike are relatively common and likely have consequences for the local population dynamics.